2013
DOI: 10.4314/sokjvs.v11i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Brucella antibodies in donkeys (<i>Equus asinus</i>) in Borno and Yobe states, Nigeria

Abstract: A cross-sectional study was designed to study the serological prevalence of antibodies against Brucella spp by using Rose Bengal Plate Test (RBPT) and Microtitre Serum Agglutination Test (MSAT). A total of six hundred (600) adult donkeys comprising of 393 males and 207 females were sampled from three local government areas each, of Konduga, Monguno and Ngala in Borno state and Bursari, Geidam and Machina in Yobe state. Overall prevalence of brucellosis was 33 (5.50%), out of which 14 (2.33%) male and 19 (3.17%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Already there are established reports that horse to horse or other animals is a less likely event and these animals do not excrete the organism (Corbel & Henry, 1983;Macmillan & Cockrem, 1985). Sadiq et al (2013) reported 5.5% seropositivity of brucellosis by RBPT and Microtiter Serum Agglutination Test in donkeys from Borno and Yobe states of Nigeria.…”
Section: Epidemiologymentioning
confidence: 99%
“…Already there are established reports that horse to horse or other animals is a less likely event and these animals do not excrete the organism (Corbel & Henry, 1983;Macmillan & Cockrem, 1985). Sadiq et al (2013) reported 5.5% seropositivity of brucellosis by RBPT and Microtiter Serum Agglutination Test in donkeys from Borno and Yobe states of Nigeria.…”
Section: Epidemiologymentioning
confidence: 99%
“…It is however higher than 5.5% (Sadiq et al, 2013) in other equines (donkey) in Borno and Yobe States by both RBPT and SAT and 4.2% in lowlands of central Oromiya, Ethiopia (Jegerfa et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of the disease in Nigeria among various animal species is reported to be 16.5% in camels (Sadiq et al, 2013), 21.3% in bovine, 11.1% in ovine and 20% in caprine (Zubairu et al, 2014). Seroprevalence rate of 11% was detected for B. abortus and 0% for B. melitensis among animal handlers, livestock keepers, butchers and middlemen (Adamu et al, 2015), while another study of the infection rate among butchers and the general public is 31.82% (Cadmus et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Brucellosis is endemic in Nigeria as shown in several serological studies in livestock (Junaidu et al, 2010;Mai et al, 2012;Nanven et al, 2013;Akinseye et al, 2016). The prevalence of 4.9% was recorded among slaughtered cattle in southwestern Nigeria (Ogugua et al, 2015a); 5.5% in donkeys in Borno and Yobe States (Sadiq et al, 2013); 14.1% in cattle screened among herds in Obudu, South-south Nigeria (Nanven et al, 2013); 0.6% in pigs in southeastern Nigeria (Onunkwo et al, 2011) and9.8% in North-central Nigeria in small ruminants (Bertu et al, 2010). In Nigeria, rearing of small ruminants is common among the rural populace.…”
Section: Introductionmentioning
confidence: 99%